Frequency of sexual activity and cardiovascular risk in subjects with erectile dysfunction: cross‐sectional and longitudinal analyses. (11th October 2013) - Corona, G.; Rastrelli, G.; Monami, M.; Maseroli, E.; Jannini, E. A.; Balercia, G.; Sforza, A.; Forti, G.; Mannucci, E.; Maggi, M.
Summary: Erectile dysfunction (ED) is risk factor for cardiovascular (CV) events. The relationship between sexual activity and incident major adverse cardiovascular events (MACE) in subjects at high CV risk is conflicting and never investigated in ED subjects. The aim of this study was to investigate relationships between frequency of sexual attempts and incident MACE and to retrospectively explore its main determinants in subjects with sexual dysfunction. A consecutive series of 2187 subjects (mean age 49.9 ± 11.6 years old) attending the Outpatient Clinic for sexual dysfunction was retrospectively studied. A subset of the previous sample ( N  = 1687) was enrolled in a longitudinal study. Frequency of sexual intercourse (coital and non‐coital) was assessed using a standard question ('During the last 3 months how many sexual attempts per month did you have?'). In the whole sample, sexual attempts were an age‐ and testosterone‐dependent phenomenon, while no association between frequency of sexual intercourse and ED or premature and delayed ejaculation, was observed. However, when the same analysis was performed according to age tertiles (I = 17–46, II = 47–59, III = 60–88 years old), ED was significantly associated with a higher risk of reduced sexual intercourse in younger (hazard ratio = 1.857 [1.066–3.234]; p  = 0.029), but not in middle‐aged or older individuals. The marital component, as assessed by SIEDY Scale 2, played a major role in regulating sexual frequency in all age bands. Depressive symptoms represent another independent risk factor for reduced sexual activity (adj r  = −0.139; p  < 0.0001), in an age‐dependent manner. When longitudinal data were analysed, a higher frequency of sexual intercourse significantly reduced the risk of MACE even after adjusting for known CV risk factors for this cohort. Identifying among mild‐to‐moderate ED subjects those with lower frequency of sexual activity might provide an opportunity to modify their behaviour and to discover subthreshold comorbidities, possibly preventing forthcoming CV events.